Rock Fractures Characterization in Khairi Murat Range, Sub Himalayan Fold and Thrust Belt, North Pakistan - Dasti, N.; Akram, S.; Akram, S.; Ahmad, I.; Ahmad, I.; Usman, M.; Usman, M. (The Nucleus, 2018)
The Potwar fold and thrust belt is an area of active oil and gas exploration and production. Fractures are the main contributors toward permeability and enhancing hydrocarbon productivity particularly in carbonates in the region. The migration and accumulation data from the hydrocarbon reservoirs indicate a well-developed fracture system in the area. 2700 individual fractures were measured along 106 scanlines, and 1260 fractures were measured at 27 sample stations using the circle inventory method. 8 fracture sets, named as â€œset-1â€ to â€œset-8â€ have been identified in the study area. Fracture properties i.e. spacing, aperture, density, porosity and permeability are estimated, which ranges from 8 m-1 to 76 m-1, 1.1 cm to 13.4 cm, 0.04 cm-1 to 0.22 cm-1, 0.06% to 2.30% and 0.24Ã—08 Darcy to 1446Ã—108 Darcy respectively. A wide range of fracture orientations occurs, creating connected fractures networks. The directional character of connectivity depends upon the direction of the dominant fractures orientation, i.e.,Â NE-SW and NW-SE. The fracture aperture and spacing data show that these parameters statistically follow the Normal and log-Normal distributions respectively.Â The maximum values of fracture porosity (2.30%), fracture permeability (1446.114Ã—108 D) and density (0.217 cm-1) of fractures are related to the vicinity of faults and regionally extended lineaments. Three fracture sets have also been identified and established their relationship with the tectonic stress field in the study area. It is concluded that this study would enhance the data for hydrocarbon production and exploring the groundwater prospects in the area.